1990
DOI: 10.1128/jb.172.3.1174-1179.1990
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of conjugative pili: monoclonal antibodies as probes for structural variants of F pili

Abstract: The lac-tra operon fusion plasmid pTG801 contains the known F plasmid DNA transfer (tra) genes required by Escherichia coli to elaborate functional F pili (T. Grossman and P. M. Silverman, J. Bacteriol. 171:650-656, 1989). Here, we show that these pili are actually structural variants of normal F pili and that the F plasmid must contain additional genes that affect pilus structure and function. We confirmed a previous report that two monoclonal antibodies that recognize epitopes at and near the amino terminus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Since the pilin polypeptide expressed by phage EDX134 reacted poorly with polyclonal anti-pilus serum, Laine et al (23) suggested that acetylation of pilin subunits might require traG, the only F locus known to affect F piliation that was not expressed by the phage. Subsequent electron microscope analyses reported by Grossman et al (12) supported this suggestion, since F-pilus filaments expressed by pTG801 hosts appeared to react with both JEL92 and JEL93. As this plasmid expresses a tra segment extending from the PstI site in traY to the EcoRI site in traG (13), its products should differ from EDX134 products only in including the TraG polypeptide required for piliation.…”
Section: Resultssupporting
confidence: 54%
“…Since the pilin polypeptide expressed by phage EDX134 reacted poorly with polyclonal anti-pilus serum, Laine et al (23) suggested that acetylation of pilin subunits might require traG, the only F locus known to affect F piliation that was not expressed by the phage. Subsequent electron microscope analyses reported by Grossman et al (12) supported this suggestion, since F-pilus filaments expressed by pTG801 hosts appeared to react with both JEL92 and JEL93. As this plasmid expresses a tra segment extending from the PstI site in traY to the EcoRI site in traG (13), its products should differ from EDX134 products only in including the TraG polypeptide required for piliation.…”
Section: Resultssupporting
confidence: 54%
“…Additionally, filaments observed in bacterial cultures, without purification, and composed of acetylated subunits tend to remain isolated, with little tendency to aggregate, whereas those composed of unacetylated subunits form massive aggregates (Grossman and Silverman, 1989). Finally, while cells expressing unacetylated F-pilin are sensitive to donorspecific RNA bacteriophages, which adsorb to the pilus sides, bacteriophage binding to pili composed of unacetylated subunits is difficult to visualize by electron microscopy, suggesting a reduction in affinity (Grossman et al, 1990). Addition of traX plasmids to cells elaborating pili composed of unacetylated subunits at least partially complemented all of these defects (T. Grossman and P. M. Silverman, unpublished).…”
Section: Structure Of Filament F-pilinmentioning
confidence: 99%
“…However, at least in some conditions, domain I is available to antibodies only when the ␣-amino group of the amino-terminal alanine residue is not acetylated. Normally, when acetylation occurs in a reaction requiring the traX gene product (Maneewannakul et al, 1995), domain I appears to be masked, in so far as antibodies to domain I epitopes fail to bind, as judged by immunogold electron microscopy (Frost et al, 1986;Grossman et al, 1990). Additionally, filaments observed in bacterial cultures, without purification, and composed of acetylated subunits tend to remain isolated, with little tendency to aggregate, whereas those composed of unacetylated subunits form massive aggregates (Grossman and Silverman, 1989).…”
Section: Structure Of Filament F-pilinmentioning
confidence: 99%
See 2 more Smart Citations